Dielectric Responses of Polyurethane Films Related to Temperature and Frequency - Hwang, Seung Won; Shin, Min Jae; Shin, Jae Sup; Kim, Chy Hyung (Bulletin of the Korean Chemical Society, 2017)
The dielectric properties of polyurethane were investigated at the temperature range of −170 to 100°C and at the frequency range of 0.01 Hz to 3 kHz. Two dielectric relaxations were observed related to the glass transition of the soft segments (α‐relaxation) close to −15°C and related to the mobility of the extender connecting the hard segments (I‐relaxation) near 50–85°C. For α‐relaxation process, the relaxation time, τ = 0.012 and 5.3 × 10−3 s for a film of 2.2 mm and 42 µm in thickness at −15°C were estimated. As temperature increased, the newly appeared I‐relaxation at the temperatures above 25°C resulted in a different relaxation process. The two relaxations followed the temperature–frequency superposition principle with different shifting factors. The polyurethane films with two different thicknesses exhibited equivalent types of relaxations but different relaxation times and shifting rates depending on their intermolecular arrangements. They showed stable dielectric responses and losses under varied DC bias electric fields.